Acid freezes uricolysis in addition to glycolysis: Utility of fluoride-EDTA-citrate tube in the measurement of uric acid for patients administered rasburicase. (May 2022) - Kalaria, Tejas; Fenn, Jonathan; Whitmill, Richard; Ford, Clare; Gama, Rousseau
Background: In samples from patients administered rasburicase, ex vivo uricolysis leads to spuriously low uric acid results. The manufacturer's recommendation of storing the sample in ice-water until analysis, however, does not fully arrest uricolysis. Since uricase activity is affected by pH and metal chelators, we assessed uricolysis inhibition in sodium fluoride-ethylenediaminetetraacetic acid (EDTA)-citrate sample tube (FC Mix tube, Greiner) used primarily for plasma glucose. Method: A serum pool was spiked with rasburicase and uric acid measured at 15, 45, 90, 150, 240 and 1080 min in a lithium heparin tube in ice-water, plain tube at room temperature (RT), EDTA tube at RT, FC Mix tube in ice-water, FC Mix tube at RT and FC Mix tube at RT prepared by dissolving FC Mix in serum. Results: The rate of urate decay was lowest in the FC Mix tube independent of temperature, then lithium heparin tube in ice-water, then EDTA tube at RT and highest in the plain tube at RT. Uric acid concentrations in the prepared FC Mix tube at RT and heparin tube in ice-water were, respectively, 98.2% and 93.8% of control values at 90 min, 97.1% and 89.3% of control values at 4 h, and remained higher in the prepared FC Mix tube at all time points. Conclusion: NaF-EDTA-citrate mixture largely arrested rasburicase mediated ex vivo uricolysis without the need for sample cooling. We propose that sample tubes containing NaF-EDTA-citrate be used for the measurement of uric acid in patients administered rasburicase.